Delays in the treatment of cauda equina syndrome due to its variable clinical features in patients presenting to the emergency department. Issue 1 (20th December 2006) - Jalloh, Ibrahim; Minhas, Pawan
Abstract : Objective: To identify reasons for delay in management of patients with cauda equina syndrome (CES) and to determine commonly presented features of CES. Methods: Retrospectively, the presenting features and management of patients treated for CES over a 4-year period were reviewed. Results: Reasons for delay in treatment were identified in over half of the patients. Discussion: Most patients do not present with all the characteristic features of CES. Sacral sensory loss is a sensitive and relatively specific sign for diagnosing CES.